Analysis of the Impact of UI/UX Elements on User Satisfaction and Loyalty In E-Commerce Platforms: An Empirical Study on the Tokopedia Platform - Annisa Triana Talmera; Mahendra Wardhana; Vita Ratnasari (International Journal Labs, 2025)
The increasingly intense competition in Indonesia's e-commerce industry is compelling platforms like Tokopedia to shift from price war strategies to enhancing user experience to build long-term loyalty. This study aims to analyze the influence of User Interface (UI) and User Experience (UX) elements on User Satisfaction and User Loyalty on the Tokopedia platform. Specifically, this research also examines the mediating role of User Satisfaction in the relationship between UI/UX and User Loyalty. This research utilizes a quantitative approach with non-probability sampling through a purposive sampling technique. Data were collected via an online questionnaire distributed to 150 active Tokopedia users residing in the Jabodetabek area. The data analysis technique used is Partial Least Squares Structural Equation Modeling (PLS-SEM) with the SmartPLS 4 software. The results indicate that User Interface (UI) and User Experience (UX) have a positive and significant effect on User Satisfaction. Subsequently, User Satisfaction is also proven to have a positive and significant effect on User Loyalty. However, the key finding of this research is the insignificance of the direct effects of UI and UX on User Loyalty. Further analysis confirms the role of User Satisfaction as a full mediation variable. This indicates that the entire influence of UI and UX on User Loyalty is fully channeled through User Satisfaction. This study concludes that satisfaction is a crucial strategic bridge that must be crossed to convert a good user experience into tangible customer loyalty. The implication for Tokopedia is that investments in UI/UX improvements will not be effective in increasing loyalty if they are not accompanied by strategies that ensure these features genuinely satisfy users first.